Penyuluhan Tentang Rumah Sehat dalam Upaya Pencegahan Penyakit Berbasis Lingkungan di Kelurahan 26 Ilir Palembang Tahun 2023 - Santi Rosalina; Heriziana. Hz; Hamyatri Rawalilah (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2023)
The house is a physical structure or building for shelter, where the environment is useful for physical and spiritual health and social conditions for both family and individual health. Home is not only a place to unwind after a day of work and doing daily activities outside the home, but home is a very important place to rest and gather with healthy, prosperous and happy family members. A healthy house is a house that has certain requirements that don't have to be big and luxurious, but a healthy house that meets the following criteria, namely that the house must have lighting, sufficient space for movement, ventilation and away from noise. The house is also a place for family members to relax. meet and communicate well and smoothly, apart from that a good house must have clean water facilities, latrines, sewage and trash cans, so as to prevent disease transmission